2022
DOI: 10.1186/s13098-022-00930-w
|View full text |Cite
|
Sign up to set email alerts
|

Age patterns of nonalcoholic fatty liver disease incidence: heterogeneous associations with metabolic changes

Abstract: Background As the nonalcoholic fatty liver disease (NAFLD) epidemic matures, understanding how metabolic changes in NAFLD development vary over the age distribution is important to guide precise prevention. We aimed to clarify metabolic trends in age-specific NAFLD incidence. Methods We conducted a 4-year longitudinal retrospective cohort study enrolling 10,240 consecutive healthy individuals who received annual physical examination during 2012–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In Chinese populations, the highest incidence of NAFLD was in individuals aged younger than 50 years. 24 Hence, this finding may hold importance in raising awareness and altering perceptions among the Chinese population regarding early and new-onset NAFLD. Similar to our findings, another study 25 found that with an increase in the age of new-onset NAFLD, the risk of diabetes decreased, with the relative risk decreasing from 3.992 at age 30 years to 1.908 at age 60 years.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In Chinese populations, the highest incidence of NAFLD was in individuals aged younger than 50 years. 24 Hence, this finding may hold importance in raising awareness and altering perceptions among the Chinese population regarding early and new-onset NAFLD. Similar to our findings, another study 25 found that with an increase in the age of new-onset NAFLD, the risk of diabetes decreased, with the relative risk decreasing from 3.992 at age 30 years to 1.908 at age 60 years.…”
Section: Discussionmentioning
confidence: 92%
“…On further exploration, we found that risk factors, incidence, and characteristics of patients with NAFLD differed by age group. In Chinese populations, the highest incidence of NAFLD was in individuals aged younger than 50 years . Hence, this finding may hold importance in raising awareness and altering perceptions among the Chinese population regarding early and new-onset NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…A low inverse correlation between the age and liver MRI-PDFF was observed (Pearson correlation r = −0.18, p = 0.08), which is consistent with a previously reported inverse correlation between the age and patients with NAFLD in the general population. 25 Thus, an age matched study in populations with and without NAFLD is warranted. Lastly, the ultrasound scanner hardware and software used in the study were designed by a single ultrasound vendor.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there are statistically significant differences in ages between weight change pattern subgroups. Previous studies indicated that the prevalence and incidence of NAFLD increased with age in a stepwise manner [34,35]. It can be explained that with age increasing, subcutaneous adipose tissue dysfunction would be induced via the accumulation of senescent adipocytes, impaired preadipocyte development, and reduced mitochondrial activity which leads to the incidence of NAFLD [36][37][38].…”
Section: Discussionmentioning
confidence: 99%